TEACHERS’ STRATEGIES AND CHALLENGES IN IMPLEMENTING HIGHER-ORDER THINKING SKILLS (HOTS) IN EFL READING INSTRUCTION: A CASE STUDY OF AN INDONESIAN SENIOR HIGH SCHOOL - Rival Raboy; Yuwin Rustam Saleh; Titin Suhartini Kaaba; Marina Pakaja; Andiani Rezkita Nabu (English Education Department at FKIP Nommensen University, 2026)
This study explores the implementation of Higher-Order Thinking Skills (HOTS) in reading instruction at the senior high school level, focusing on teachers’ practices and the challenges encountered during the learning process. A qualitative descriptive design was employed, involving one English teacher at SMAN 1 Kabila selected through purposive sampling. Data were collected through semi-structured interviews, one month of classroom observations across seven learning sessions, and documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that HOTS was implemented through structured lesson planning, open-ended questioning, differentiated instruction, and interactive learning activities. Three HOTS dimensions were identified in classroom practice: analyzing, evaluating, and creating. Students demonstrated analyzing skills by interpreting information and examining relationships between ideas, evaluating skills by justifying opinions with logical reasons and responding to alternative viewpoints, and creating skills by generating new ideas and products based on the texts they read. The study also identified major challenges, including differences in students’ abilities and learning styles, as well as limited instructional time for facilitating higher-order thinking activities. This study contributes to HOTS implementation research by providing empirical evidence of how HOTS is enacted in classroom reading practices and by highlighting the instructional strategies and challenges experienced by teachers in fostering higher-order thinking in EFL reading contexts.